Analisis Penerapan Pajak Pertambahan Nilai pada Pajak Masukan Lebih Bayar : Studi Kasus pada PT. Polindo Solusi Nusantara - Kartika, Yunita (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The proper implementation of Value Added Tax (VAT) is crucial for ensuring compliance with tax regulations and optimizing fiscal responsibilities within a company. This research investigates the application of VAT, specifically in handling Input VAT Overpayment, at PT. Polindo Solusi Nusantara. The study is driven by the need to assess whether the company's VAT practices align with Law No. 42 of 2009 concerning VAT. Using a quantitative approach and descriptive method, the research analyzes the company’s financial reports from 2013 to 2014. Findings reveal that the company accurately calculated Input and Output VAT based on applicable rates. However, it failed to report Output VAT within the required period and did not compensate overpaid Input VAT into the following tax periods. This administrative shortcoming led to missed tax optimization opportunities and incurred penalties due to late tax return submissions. Although the VAT mechanism applied by the company generally aligns with the legal framework, it still requires improvements in timely reporting and procedural compliance. The findings imply that strengthening tax administration and increasing awareness of VAT regulations are essential to prevent future inefficiencies and penalties.